The Effects of Aging Period and Freezing Sequence on Consumer Palatability Ratings, Tenderness, and Color Stability of Longissimus Dorsi, Semitendinosus, and Biceps Femoris Steaks - Taylor M. Dieball; Greta E. Huber; Samuel F. Stickley; Kiersten M. Gundersen; Kasey R. Maddock Carlin; Morgan D. Zumbaugh; Michael D. Chao; Jessie L. Vipham; Travis G. O'Quinn; Erin S. Beyer (Kansas Agricultural Experiment Station Research Reports, 2025)
Objective: The objective of this study was to examine the effect of freezing and aging sequence on palatability, overall tenderness, and objective color readings of three different beef muscles and two aging periods. Study Description: The longissimus dorsi (LD), semitendinosus (ST), and biceps femoris (BF) were fabricated into 1-in steaks and assigned to one of the following treatment combinations: age (21 days) then freeze, freeze then age (21 days), age (28 days) then freeze, or freeze then age (28 days). Consumers evaluated samples for flavor, juiciness, tenderness, overall liking, and acceptability for each sensory trait. Samples designated for Warner-Bratzler shear force (WBSF) were allowed 20 minutes to bloom for raw color evaluation and then cooked for analysis. Results: The freezing treatment or aging period did not impact (P > 0.05) consumer sensory rating of tenderness, flavor, or overall liking. The consumers rated the LD as the juiciest (P < 0.05) compared to the ST and BF. As expected, the LD resulted in the highest (P < 0.05) tenderness rating for the consumer. The LD had the lowest (P < 0.05) WBSF values, indicating it was the most tender. Within flavor, the consumers rated the LD as the most flavorful (P < 0.05) followed by the ST, and then the BF. For raw and cooked color, the L* (lightness) values differed (P < 0.05) between all main effects, including freezing treatments (Age Freeze > Freeze Age), aging periods (21 days > 28 days), and muscle (ST > LD > BF). These results showed freezing and then aging or aging and then freezing does not affect palatability or shear force values. This indicates that reversing the freezing order is not an effective way to improve the tenderness of historically tough muscles. The Bottom Line: The results indicate reversing the typical age and freezing order does not improve tenderness and therefore is not a valid way to improve palatability of historically tough muscles.
Keywords: beef; freezing; palatability